2021
DOI: 10.3390/jcm10020348
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors to Perinatal Outcome in Pregnancies with Gestational Diabetes—What Matters Most? A Retrospective Analysis

Abstract: The aim of diabetes care of pregnant women with gestational diabetes mellitus (GDM) is to attain pregnancy outcomes including rates of large-for-gestational-age (LGA) newborns, pre-eclampsia, C-sections (CS) and other neonatal outcomes similar to those of the non-GDM pregnant population. Obesity and excessive weight gain during pregnancy have been shown to also impact perinatal outcome. Since GDM is frequently associated with elevated body mass index (BMI), we evaluated the impact of maternal prepregnancy BMI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
2
13
0
10
Order By: Relevance
“…A few studies suggest that GDM is not associated with the occurrence of PE after removing the effect of pre pregnancy BMI and other factors ( 42 46 ). A retrospective cohort study in Germany showed that there was no independent correlation between GDM and PE, regardless of obesity before pregnancy, and it was unknown whether it was related to the strict control of blood glucose levels ( 45 ). In studies conducted in Australia and Japan ( 42 , 43 ), cases included those within the diagnostic criteria of IADPSG but not up to their own national standards, so blood glucose levels were relatively low, which may have affect the results.…”
Section: Correlation Between Gdm and Pementioning
confidence: 99%
“…A few studies suggest that GDM is not associated with the occurrence of PE after removing the effect of pre pregnancy BMI and other factors ( 42 46 ). A retrospective cohort study in Germany showed that there was no independent correlation between GDM and PE, regardless of obesity before pregnancy, and it was unknown whether it was related to the strict control of blood glucose levels ( 45 ). In studies conducted in Australia and Japan ( 42 , 43 ), cases included those within the diagnostic criteria of IADPSG but not up to their own national standards, so blood glucose levels were relatively low, which may have affect the results.…”
Section: Correlation Between Gdm and Pementioning
confidence: 99%
“…Maternal weight and body mass indices were significantly higher in our study cohort compared to a collective of normal controls, which could be expected since obesity is one of the major risk factors for developing GDM [ 1 ]. In fact, in previous studies we observed a higher impact of maternal body mass indices and weight gain during pregnancy on maternal and perinatal outcomes, irrespective of the diagnosis of GDM, than by the diagnosis of GDM alone [ 25 , 26 ]. On the contrary, neonatal outcome was favorable in our cohort, and did not observe significant differences in comparison to controls.…”
Section: Discussionmentioning
confidence: 88%
“…Das Risiko für ein für die Schwangerschaftswoche zur Geburt zu schweres Kind ist dabei auch von der Gewichtszuahme der Mutter in der Schwangerschaft und vom Ausgangs-BMI der Mutter abhängig [6]. In der multivariaten Analyse zeigt sich dabei, dass die Diagnose GDM bei gut eingestelltem Diabetes einen geringeren Einfluss auf das Kindsgewicht hat, als die übermäßige Gewichtszunahme in der Schwangerschaft.…”
unclassified
“…In der multivariaten Analyse zeigt sich dabei, dass die Diagnose GDM bei gut eingestelltem Diabetes einen geringeren Einfluss auf das Kindsgewicht hat, als die übermäßige Gewichtszunahme in der Schwangerschaft. Die übermäßige Gewichtszunahme ist durch ein Überschreiten der BMI-abhängigen Empfehlung zur Gewichtszunahme in der Schwangerschaft definiert [6]. Untersuchungen haben gezeigt, dass die Gewichtszunahme bei Schwangeren mit GDM signifikant niedriger war und in der Gruppe der Schwangeren mit einem BMI > 30 kg/m 2 signifikant seltener eine exzessive Gewichtszunahme berichtet wurde [6].…”
unclassified
See 1 more Smart Citation